Mindfulness, Self-Compassion, Resilience, and Academic Anxiety among College Students: A Structural Equation Modeling Approach - Sujadi, Eko (Tarbawi : Jurnal Ilmu Pendidikan, 2022)
One of the challenges faced by students is academic anxiety, which can have negative impacts on their academic activities. The aim of this study was to examine the direct effects of mindfulness, self-compassion, and resilience on academic anxiety, as well as the mediating role of resilience in these relationships. A cross-sectional study was conducted, and a sample of 344 university students from Jambi Province, Indonesia was recruited to complete the Academic Anxiety Scale (AAS), Five Facet Mindfulness Questionnaire (FFMQ), Self-Compassion Scale (SCS), and Brief Resilience Scale (BRS). The structural model was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The study revealed that there were significant negative effects of mindfulness, self-compassion, and resilience on academic anxiety. Additionally, the findings indicated that resilience acted as a mediator in these relationships. This study has implications for the importance of preventing and managing academic anxiety among students by enhancing mindfulness, self-compassion, and resilience. Counseling services in universities should be maximized to address this issue.